2019
DOI: 10.2174/0929866526666190228163629
|View full text |Cite
|
Sign up to set email alerts
|

Lytic Polysaccharide Monooxygenase from Aspergillus fumigatus can Improve Enzymatic Cocktail Activity During Sugarcane Bagasse Hydrolysis

Abstract: Background: Lytic Polysaccharide Monooxygenases (LPMOs) are auxiliary accessory enzymes that act synergistically with cellulases and which are increasingly being used in secondgeneration bioethanol production from biomasses. Several LPMOs have been identified in various filamentous fungi, including Aspergillus fumigatus. However, many LPMOs have not been characterized yet. Objective: To report the role of uncharacterized A. fumigatus AfAA9_B LPMO. Methods: qRT-PCR analysis was employed to analyze the LPMO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 63 publications
1
15
1
2
Order By: Relevance
“…To identify enzyme components that may be lacking in cellulase cocktails, commercial cellulase mixtures have also been supplemented with fungal culture broths or (semi)purified enzyme components. Celluclast has been studied extensively in spiking studies, revealing the positive impact of xylanase, mannanase and LPMO supplementation on the efficiency of cellulose saccharification [81,87,143,177,250,272,382], as also discussed above. In some cases, in-house fungal (e.g., T. reesei) culture broths have been used to showcase the positive effect of selected enzymes, such as three AA9s from Geotrichum candidum [205] or two AA14 LPMOs from Pycnoporus coccineus [68], on saccharification efficiency.…”
Section: Spiking Studies To Highlight Enzyme Activities Lacking In Comentioning
confidence: 90%
“…To identify enzyme components that may be lacking in cellulase cocktails, commercial cellulase mixtures have also been supplemented with fungal culture broths or (semi)purified enzyme components. Celluclast has been studied extensively in spiking studies, revealing the positive impact of xylanase, mannanase and LPMO supplementation on the efficiency of cellulose saccharification [81,87,143,177,250,272,382], as also discussed above. In some cases, in-house fungal (e.g., T. reesei) culture broths have been used to showcase the positive effect of selected enzymes, such as three AA9s from Geotrichum candidum [205] or two AA14 LPMOs from Pycnoporus coccineus [68], on saccharification efficiency.…”
Section: Spiking Studies To Highlight Enzyme Activities Lacking In Comentioning
confidence: 90%
“…Studies have shown that adding LPMOs to cellulase cocktails can improve the degradation efficiency of cellulose biomass and reduce the required enzyme amount (de Gouvea et al 2019;Dimarogona et al 2013;Harris et al 2010;Hemsworth et al 2015;Zhang et al 2019). It is speculated that this synergy is due to the oxidative cleavage of polysaccharide crystalline regions by LPMOs, which provides more accessible sites for glycoside hydrolases ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the (putative) LPMOs of A. tamarii have not gained much attention. With regard to putative LPMOs from aspergilli, LPMO activity has been shown, to date, for five AA9s from A. fumigatus [27,28], seven AA9s from A. terreus [27], two AA9s [29,30] and one AA13 [31] from A. nidulans, an AA9 from A. niger [32], an AA11 [33] and AA13 [31] from A. oryzae, and an AA16 from A. aculeatus [34], whereas structural data are available for an AA9 (AfAA9B) from A. fumigatus [35] and an AA11 [33] and AA13 [31] from A. oryzae. So far, xyloglucan activity by these LPMOs has remained unexplored, except for one LPMO from A. nidulans (AN3046) for which xyloglucan activity has been proposed [29].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to putative LPMOs from aspergilli, LPMO activity has been shown, to date, for five AA9s from A . fumigatus [ 27 , 28 ], seven AA9s from A . terreus [ 27 ], two AA9s [ 29 , 30 ] and one AA13 [ 31 ] from A .…”
Section: Introductionmentioning
confidence: 99%